Numerical study of turbulent flow inside a spark ignition engine cylinder. (2016) - Beauquel, J.A.; Ibrahim, S.S.; Chen, Rui
This paper presents the computational fluid dynamics (CFD) modelling results of the transient flow inside an engine cylinder with spark ignition valve timing. Transient flow simulations at 1, 500 rpm are conducted and take into account the movement of the inlet, exhaust valves and the piston. The simulated in-cylinder velocities are compared to published laser Doppler anemometry (LDA) experimental data which is re-processed to illustrate the time history of mean velocities for all LDA measured points. Using the k-ε RNG turbulence model, the numerical prediction seems in good agreement with the LDA measurements with an overall averaged correlation of 78.3% for the intake and compression stroke. The development of the flow pattern inside the cylinder at the symmetrical cross-section is presented where the tumble motions and their centre are described for 90 and 180 crankshaft angle degrees (CAD).